Factors and Predictors of Online Security and Privacy Behavior - Bubaš, Goran; Orehovački, Tihomir; Konecki, Mario (Journal of Information and Organizational Sciences, 2008)
Assumptions and habits regarding computer and Internet use are among the major factors which influence online privacy and security of Internet users. In our study a survey was performed on 312 subjects (college students who are Internet users with IT skills) that investigated how assumptions and habits of Internet users are related to their online security and privacy. The following four factors of online security and privacy related behaviors were revealed in factor analysis: F1 – conscientiousness in the maintenance of the operating system, upgrading of the Internet browser and use of antivirus and antispyware programs; F2 –engagement in risky and careless online activities with lack of concern for personal online privacy; F3 – disbelief that privacy violations and security threats represent possible problems; F4 – lack of fear regarding potential privacy and security threats with no need for change in personal online behavior. Statistically significant correlations were found between some of the discovered factors on the one side, and criteria variables occurrence of malicious code (C1) and data loss on the home computer (C2) on the other. In addition, a regression analysis was performed which revealed that the potentially risky online behaviors of Internet users were associated with the two criteria variables. To properly interpret the results of correlation and regression analyses a conceptual model was developed of the potential causal relationships between the behavior of Internet users and their experiences with online security threats. An additional study was also performed which partly confirmed the conceptual model, as well as the factors of online security and privacy related behaviors.